IDENTIFIKASI Streptococcus mutans PADA PENGGUNA KAWAT GIGI - Rizka Meisya Putri; Yusianti Silviani (Klinikal Sains : Jurnal Analis Kesehatan, 2026)
The use of fixed orthodontic appliances (braces) contributes to increased plaque and debris accumulation on the tooth surface, which may disrupt the oral microbial balance and promote the proliferation of cariogenic bacteria, including Streptococcus mutans. This study was conducted to identify Streptococcus mutans in individuals wearing braces. The research employed a descriptive observational design with a cross-sectional approach by means of purposive sampling. Samples consisted of swabs from the braces of 14 participants, including 12 users, 1 positive control, and 1 negative control. Bacterial identification was carried out through cultivation in Kaldu Peptone Darah (KPD), isolation on Blood Agar Plates (BAP), gram staining, and biochemical testing. Data were analyzed descriptively. The results showed growth in all samples on KPD, with Streptococcus species dominating at 66.7%. Colony morphology, gram-positive cocci staining, negative catalase test, and carbohydrate fermentation profiles indicated that the isolates belonged to the Streptococcus viridans group. Therefore, it can be concluded that individuals wearing braces harbor Streptococcus species classified within the viridans group.